Establishing the tools for routine analysis of chloroplast dna diversity in oil palm (Elaeis spp.) - Ho, Carl Miew (2014)
Oil palm (Elaeis guineensis Jacq.), a member of family Palmae, is one of the most efficient oilseed crops in the world. In order to meet the rising global demand on palm oil, efforts have focused on enhancing oil palm breeding, developing palms resistance towards trunk and root diseases as well as on improving stress tolerance. Molecular markers can play a vital role in improving the oil palm. To date, for oil palm, molecular markers analysis has been restricted to nuclear DNA. However, due to its non-recombinant nature and uniparental inheritance, detecting useful polymorphism at population level can be meaningful for evolutionary studies as well as to characterize the diversity of oil palm chloroplast DNA (cpDNA). Studies of chloroplast DNA diversity can reveal insights into the evolutionary and domestication history of a species. In this study, the development of an approach for isolating enriched oil palm cpDNA was a necessity in order to be able to analyze the variations present in oil palm cpDNA of selected palm germplasms. An enrichment cpDNA protocol using the combination method of sucrose gradient and cesium chloride gradient separation was adopted in order to isolate oil palm chloroplast DNA. A total of six oil palm germplasm collections (namely Angola, Ghana, Nigeria,Madagascar, Costa Rica and Suriname) were selected and the cpDNA was extracted using modified cpDNA enrichment protocol. The protocol first isolated the organelle and then using isopycnic centrifugation, cpDNA was purified. The extracted enriched oil palm cpDNA was initially verified using restriction enzyme analysis. To characterize the diversity of oil palm cpDNA, chloroplast microsatellite (cpSSR) primers were developed from chloroplast derived sequences obtained from the hypomethylated regions of oil palm as well as from the sequences reported in the published E. guineensis chloroplast genome in Gen Bank. Three chloroplast universal primers were also employed to analyze the diversity of oil palm cpDNA. In order to further validate the reliability of extraction protocol and cpSSR primers, PCR amplicons of a small subset of samples were sequenced. The sequencing results were then searched against public databases. Subsequently, twelve pairs of oil palm cpSSR and two chloroplast- specific universal primers were used to genotype the cpDNA diversity. The positive allele frequencies of the microsatellites locus for the five germplasms ranged from 0.2 to 1.0. The Madagascar germplasm with positive allele frequencies ranging from 0.22 to 0.89 demonstrated the greatest diversity among the other five germplasm collections analyzed in this study. Moreover, one polymorphic oil palm cpSSR primer (atp1) demonstrated interspecific positive band variation between E. guineensis Jacq. and E. oleifera Cortez. The level of SSR polymorphism detected within species was low suggesting that the rate of molecular evolution in oil palm cpDNA was relatively low. However, higher levels of cpDNA polymorphisms between Elaeis species were detected.